PROMOTING ADMUNICATOR'S COMMUNICATION IN EXTRACURRICULAR WORK - L.V. Petko (Academy of Cognitive and Natural Sciences, 2007)
The article is discovered understanding of "communicative " of teenager's personality and its stimulation in process of touristic activity in the educational process in the comprehensive school.